Assessment of Architecture Students’ Knowledge of Passive Design Strategies in Academic Buildings in a Typical Nigerian Private University - Olasupo, O.; Obaleye, O. J.; Rotimi, E.; Usman, S.; Ojeleye, O. I.; Akinola, G. A. (NIU Journal of Humanities; Vol. 8 Núm. 4 (2023): NIU Journal of Humanities, Vol. 8 No. 4, December 2023DO - 10.58709/niujhu.v8i4.1738, 2023)
Abstract . Buildings use more than 40% of the energy consumed worldwide. This has prompted the development of numerous strategies to guarantee that buildings can still function maximally with reduced energy use. The concept of passive design strategies has been widely employed in architectural professional practice to ensure the reduction of building energy usage is kept to a minimum and enhance building performance. In architectural design training, however, despite the study of building climatology, several students are still seen designing buildings in tropical climates with little adoption of passive design strategies. To this end, this study aims at assessing the knowledge level of graduate architecture students at Lead City University, Ibadan, Oyo State of passive design strategies in academic buildings. The case study research approach was used, and respondents were chosen through random sampling. A total of 84 students were given structured questions to answer in order to collect primary data. Data were analysed using frequencies and percentages in SPSS, and the results were presented using tables. Respondents’ level of awareness and importance of the various concepts associated with passive design in academic buildings were considered. The study revealed that respondents have good knowledge about passive design strategies. Building materials, day lighting, and natural ventilation were identified as the most crucial among the passive design strategies used for academic buildings in achieving users' comfort and reducing energy conservation. Also, building mass was observed to be considered the least important among the passive design strategies. Keywords : Academic building, Architecture students, Design strategies, Passive design, Thermal comfort.